La dimension spatiale de l’achat en ligne - Leslie Belton-Chevallier; Benjamin Motte-Baumvol; Frédéric de Coninck (Netcom)
The spread of online shopping examines the potential spatial specificities of household practices and uses of this channel of purchasing. More precisely, the article aims to understand the peri-urban dimension of these practices by placing them in a socio-spatial context. Based on both quantitative (questionnaires) and qualitative (interviews) field work, we shall see that peri-urban households are bigger users of e-commerce and home delivery than their urban counterparts. This greater propensity for buying online forms part of the continuity of daily practices based on the principle of a search for efficiency or cutting down on travelling, even avoiding the town or its negative impacts at the very least.